A challenging presentation of invasive nasopharyngeal sarcomatoid carcinoma. Issue 7 (8th July 2019) - Yao, Alexander; Saeed, Haroon; Udall, Gavin; Kaushik, Vivek; Lee, Lip Wai
Abstract : Sarcomatoid carcinoma is a rare clinical entity, especially when presenting in the nasopharynx. We describe the first documented case of nasopharyngeal sarcomatoid carcinoma with intracranial extension in a 59-year-old Caucasian man presenting with severe bifrontal headache and diplopia, secondary to left abducens nerve palsy. We highlight some of the major diagnostic challenges and describe its unusual histological appearance. We outline the importance of a multidisciplinary approach to his management, which includes input from the medicine, neurosurgery, Ear, Nose and Throat (ENT), pathology, radiology, oncology and respiratory teams. In the context of limited evidence, we then describe the rationale to proceed with induction chemotherapy followed by concurrent chemoradiotherapy. Although there was a partial response to treatment, it was not sufficient enough to allow subsequent surgical clearance. The plan going forward is to palliate with chemotherapy as and when the disease progresses.